2019
DOI: 10.2174/1874213001912010015
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Mitigation in the Power Sector of Thailand: Analyses of Cleaner Supply-side Options Beyond the Paris Agreement

Abstract: Background: The drastically increasing share of fossil fuel supply to meet the rapidly growing electricity demand resulting in increasing Carbon dioxide (CO2) emissions, is the major concern in Thailand. In 2015, fossil fuels used in electricity generation in Thailand accounted for around 85.3% of the total electricity generation. Aim: The aim of the study is to analyze carbon dioxide mitigation options under the clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…Figure 4 shows emissions by gas and indicates that carbon dioxide is the main type of GHG emission from electricity generation in the baseline scenario. This finding is in line with a previous study [49] in which carbon dioxide was found to constitute the main type of GHG emission.…”
Section: The Ex Ante Baseline Scenariosupporting
confidence: 94%
See 4 more Smart Citations
“…Figure 4 shows emissions by gas and indicates that carbon dioxide is the main type of GHG emission from electricity generation in the baseline scenario. This finding is in line with a previous study [49] in which carbon dioxide was found to constitute the main type of GHG emission.…”
Section: The Ex Ante Baseline Scenariosupporting
confidence: 94%
“…Therefore, the full implementation of the REFIT policy would result in higher emission reductions than expected under the NDC scenario, as can be seen in Table 10. However, if placed in an international scale, these results are lower than those reported by previous studies [49][50][51]. This is as expected because REFIT policies are different.…”
Section: The Refit Policy Scenario and The Ndc Mitigation Scenariocontrasting
confidence: 74%
See 3 more Smart Citations